Modes of Play in Eighteenth-Century France - Bloom, Rori; Comsa, Maria Teodora; Curulla, Annelle; Falaky, Fayçal; Falaky, Fayçal; Hakim, Zeina; Hargrave, Katharine; Leichman, Jeffrey M.; Mandarino, Erika; McGinnis, Reginald; McGinnis, Reginald; Perras, Jean-Alexandre; et al. (Scènes francophones: Studies in French and Francophone Theater, 2021)
Collecting diverse critical perspectives on the topic of play—from dolls, bilboquets, and lotteries, to writing itself—this volume offers new insights into how play was used to represent and reimagine the world in eighteenth-century France. In documenting various modes of play, contributors theorize its relation to law, religion, politics, and economics. Equally important was the role of “play” in plays, and the function of theatrical performance in mirroring, and often contesting, our place in the universe. These essays remind us that the spirit of play was very much alive during the “Age of Reason,” providing ways for its practitioners to consider more “serious” themes such as free will and determinism, illusions and equivocations, or chance and inequality. Standing at the intersection of multiple intellectual avenues, this is the first comprehensive study in English devoted to the different guises of play in Enlightenment France, certain to interest curious readers across disciplinary backgrounds